2015
DOI: 10.1159/000370253
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of ‘Liver-First' Reverse Management for Advanced and Aggressive Synchronous Colorectal Liver Metastases: A Propensity-Matched Analysis

Abstract: Background: Although a ‘liver-first' approach recently has been advocated in treating synchronous colorectal metastases, little is known about how results compare with those of the classical approach among patients with similar grades of liver metastases. Methods: Propensity-score matching was used to select study subjects. Oncologic outcomes were compared between 10 consecutive patients with unresectable advanced and aggressive synchronous colorectal liver metastases treated with the reverse strategy and 30 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
3
12
1
Order By: Relevance
“…The completion rate of 93% in the present study was even higher than described in previous series (65 and 84%) [17][18][19][20]. Feared colonic complications such as occlusion or perforation during neoadjuvant treatment occurred only in 11% of the patients and did not preclude the completion of the whole sequence provided complications were adequately treated.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The completion rate of 93% in the present study was even higher than described in previous series (65 and 84%) [17][18][19][20]. Feared colonic complications such as occlusion or perforation during neoadjuvant treatment occurred only in 11% of the patients and did not preclude the completion of the whole sequence provided complications were adequately treated.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies reported morbidity ranging from 17 to 45% [18,[21][22][23][24][25][26][27][28], and major complication rates were 0 to 27.3% when reported [19,[22][23][24][25][26]. Our high complication rate could be explained by the aggressive surgical strategy for patients with high oncologic burden with 40% portal vein embolization and 61% major hepatectomies, compared to 11-60% portal vein embolization [18,21,22,28,29] and 36-89% major hepatecomies [18-20, 22-26, 29, 30] in other reports. However, there was no mortality within 90 postoperative days, while the highest reported mortality rate of 2% in the series from Welsh et al [19].…”
Section: Discussionmentioning
confidence: 72%
“…Their tumour burden within the liver, however, seemed to be comparable. In line with this, Tanaka et al 18 reported a 100% recurrence rate in their cohort of 10 patients with aggressive initially unresectable metastases, who underwent the liver-first approach. However, this group of patients is a highly selected population with a substantial tumour burden (also reflected by the low feasibility of 20%) and these results can therefore not be projected on a more general patient group with synchronous CRLM.…”
Section: Discussionmentioning
confidence: 74%
“…[13][14][15] However, most series contain relatively small patients numbers. [14][15][16][17][18][19] Moreover, the follow-up within these cohorts is often relatively short, 15,[17][18][19] as also in our previous series. 12 Furthermore, none of these studies provides robust data on long-term outcomes, 14,16 with regard to survival and other oncologic outcomes.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation